Opportunistic interventions for methamphetamine use: reducing the risks - Pennay, Amy; Lubman, D.; Reichert, T. (IP Communications, 2012)
Methamphetamine is the third most popular illicit drug in Australia. Over one million (6.3%) Australians report having ever tried methamphetamine, and approximately 3% are regular users (AHIW 2008). Around 11 % of regular users are likely to develop dependence to methamphetamine (equating to 73 000 Australians) (McKetin et al 2005a), underscoring the need for early detection and effective management of methamphetamine-related harms. However, methamphetamine users are less likely than other drug users to access specialist alcohol and other drug (AOD) treatment for their drug use (AIHW 2007; Klee & Morris 1994; Pennay & Lee 2009; Shearer & Gowing 2004; Wright et al 1999), highlighting the important role that other healthcare professionals (e.g. general practitioners (GPs), hospital staff and mental health workers) must play in the treatment of methamphetamine use/dependence. In this chapter, we discuss Steven, a methamphetamine user who presents to his local GP with problems related to methamphetamine use. In describing this case, important clinical and treatment issues are explored.